How family sports behavior shapes adolescent sleep: mediating effects in causation - Wu, Wenqi; Xie, Aoming; Li, Xiaotian; Xun, Yiran (Frontiers in Public Health, 2025)
ObjectiveThis study aimed to describe adolescent sleep and explore its association with physical activity, focusing on the mediating role of family physical behavior.MethodsData were sourced from the Chinese Adolescent Health Database, which included responses from 7,482 adolescents aged 12–18 years about sleep, personal physical activity, and family physical activity. Using two-stage least squares (2-SLS), we examined the relationship between adolescent sleep, personal physical activity, and father’s physical activity habits (as instrumental variables). A mediating variable, family physical behavior, was introduced to investigate causal pathways.Results2-SLS regression revealed a significant positive correlation between physical activity and sleep quality (β = 0.052, p<0.01). With the inclusion of the instrumental variable (father’s physical activity habits), the effect size increased to 0.208 (p<0.01). Adding family physical behavior as a mediating variable further increased the coefficient by 0.1437. The analysis showed that 84.62% of the total effect of physical activity on sleep was mediated, while the direct effect accounted for only 15.53%. Both F-statistics were significant.ConclusionFamily physical behaviors significantly enhance the positive impact of physical activity on adolescent sleep. Promoting family sports participation is essential for fostering healthy lifestyles and improving adolescent sleep quality. This highlights the need for interventions that incorporate family physical activities into adolescent health strategies.